Legal Certainty and Financial Inclusion Effects of POJK 29/2024 on Innovative Credit Scoring - Oremia Exilla Rafelina Sihombing; Rianda Dirkareshza (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2025)
The development of financial technology has led to the emergence of ICS as a solution to the limited access to formal credit still experienced by underbanked communities and MSME players in Indonesia. This study aims to analyze the role of ICS in increasing financial inclusion and to examine the implementation of POJK 29/2024 in supporting the optimization of ICS for MSMEs. The research method employed is normative legal research, utilizing a legislative and conceptual approach. The results demonstrate that ICS plays a crucial role in expanding credit access by leveraging AI and ML-based alternative data, thereby reaching underbanked communities and MSMEs that lack a formal credit history. In addition, POJK 29/2024 provides legal certainty and a more comprehensive governance framework for the implementation of alternative credit, particularly in relation to licensing, supervision, and consumer protection. Banks are expected to optimized the use of ICS in the credit assessment process to improve access to financing for MSMEs while continuing to apply the principle of prudence.